Reconstructing the idea of prayer space : a critical analysis of the temporary praying platform project of 2nd year architecture students in the National University of Malaysia(UKM) - Utaberta, Nangkula; Bahar, Mohammad Arsyad (International Center for Islamic Architecture from the Sunnah, Department of Architecture UIN Maulana Malik Ibrahim Malang, 2013)
God created human as caliph on this earth. Caliph means leader, care-taker and guardian. Therefore humans have an obligation to maintain, preserve and conserve this natural for future generations. Today we see a lot of damage that occurs in the earth caused by human behavior. Islam saw the whole of nature as a place of prayer that must be maintained its cleanliness and purity. Therefore as Muslims we need to preserve nature as we keep our place of prayer. The main objective of this paper is to re-questioning and re-interpreting the idea of sustainability in Islamic Architecture through a critical analysis of first project of 2nd year architecture student of UKM which is the “Temporary Praying Platform”. The discussion itself will be divided into three (3) main parts. The first part will be discussing contemporary issues in Islamic Architecture especially in the design of Mosques while the second part will expand the framework of sustainability in Islamic Architecture. The last part will be analyzing some sample of design submission by 2nd year students of UKM on the temporary praying platform project. It is expected that this paper can start a further discussion on the inner meaning in Islam and how it was implemented in the design of praying spaces in the future.